Inhibition of Pyruvate Dehydrogenase in the Heart as an Initiating Event in the Development of Diabetic Cardiomyopathy - Abdallah Elnwasany; Heba A. Ewida; Pamela A. Szweda; Luke I. Szweda (MDPI AG, 2023)
Obesity affects a growing fraction of the population and is a risk factor for type 2 diabetes and cardiovascular disease. Even in the absence of hypertension and coronary artery disease, type 2 diabetes can result in a heart disease termed diabetic cardiomyopathy. Diminished glucose oxidation, increased reliance on fatty acid oxidation for energy production, and oxidative stress are believed to play causal roles. However, the progression of metabolic changes and mechanisms by which these changes impact the heart have not been established. Cardiac pyruvate dehydrogenase (PDH), the central regulatory site for glucose oxidation, is rapidly inhibited in mice fed high dietary fat, a model of obesity and diabetes. Increased reliance on fatty acid oxidation for energy production, in turn, enhances mitochondrial pro-oxidant production. Inhibition of PDH may therefore initiate metabolic inflexibility and oxidative stress and precipitate diabetic cardiomyopathy. We discuss evidence from the literature that supports a role for PDH inhibition in loss in energy homeostasis and diastolic function in obese and diabetic humans and in rodent models. Finally, seemingly contradictory findings highlight the complexity of the disease and the need to delineate progressive changes in cardiac metabolism, the impact on myocardial structure and function, and the ability to intercede.